2010
DOI: 10.3109/00016357.2010.536907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air abrasion particles on the bond strength of adhesive resin cement to zirconia core

Abstract: Air abrasion with 30-50 μm synthetic diamond particles, 60-80 μm cubic boron nitride particles and 110 μm aluminum oxide particles showed higher bond strength values than other methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 34 publications
4
45
0
1
Order By: Relevance
“…Synthetic diamond particles is one of the alternative air abrasion material used in dentistry to increase the surface roughness and surface area of high strength ceramics [27,38]. It was reported in a related study that, 1-3 mm synthetic diamond particles would create higher surface roughness and bond strength values on the glass-infiltrated aluminum oxide ceramics than 50 mm Al 2 O 3 particles [38].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Synthetic diamond particles is one of the alternative air abrasion material used in dentistry to increase the surface roughness and surface area of high strength ceramics [27,38]. It was reported in a related study that, 1-3 mm synthetic diamond particles would create higher surface roughness and bond strength values on the glass-infiltrated aluminum oxide ceramics than 50 mm Al 2 O 3 particles [38].…”
Section: Discussionmentioning
confidence: 97%
“…The silica coating systems have showed superior bond strength values in several studies [18,26]. Nevertheless, nano-sized synthetic diamond particles have also been used as an airborne abrasive particle to modify the surface of dental materials and create more uniform and smaller cavities [27]. But, further studies must be performed to evaluate the effects of synthetic diamond particle abrasion on bonding strength of zirconium oxide ceramics.…”
Section: Introductionmentioning
confidence: 98%
“…It was previously applied onto the glass-infiltrated aluminous oxide ceramic surface to increase the surface roughness and surface area [16,17] then it was used on zirconia core, Ni-Cr and Co-Cr surface [18,19]. Several studies have shown that silicoating and functional monomer systems improve the composite-to-metal bond strength with noble and nonnoble dental alloys and with titanium and its alloys [2,8,11,19].…”
Section: Introductionmentioning
confidence: 99%
“…6 Surface treatments effect the shear bond strength of veneer ceramic and resin cement to zirconia core. [13][14][15][16] To increase shear bond strength many surface treatment methods were evaluated (sandblasting, acid etching, silica coating, primer applications). Because of the zirconia is an acid-resistant material, chemical roughening procedures do not work on the zirconia surface and other methods are required, such as sandblasting, to produce a rough surface for micromechanical bonding.…”
mentioning
confidence: 99%
“…Because of the zirconia is an acid-resistant material, chemical roughening procedures do not work on the zirconia surface and other methods are required, such as sandblasting, to produce a rough surface for micromechanical bonding. 6,[15][16][17] To improve the adhesion between the cement and zirconia core through creation of a higher surface area, sandblasting is performed. Sandblasting densely sintered zirconia creates sharp depressions and protrusions on the surface and promotes a phase transformation (from tetragonal to monoclinic).…”
mentioning
confidence: 99%